Measurement of Pyrethroid, Organophosphorus, and Carbamate Insecticides in Human Plasma using Isotope Dilution Gas Chromatography-High Resolution Mass Spectrometry - Pérez, José J. (2010)
We have developed a gas chromatography-high resolution mass spectrometry method for measuring pyrethroid, organophosphorus, carbamate and fipronil pesticides and the synergist piperonyl butoxide in human plasma. Plasma samples were extracted using solid phase extraction and were then concentrated for injection and analysis using isotope dilution gas chromatography-high resolution mass spectrometry. The limits of detection ranged from 10 to 158 pg/mL with relative recoveries at concentrations near the LODs (e.g., 25 or 250 pg/mL) ranging from 87% to 156% (9 of the 16 compounds were withing ± 15% of 100%). The extraction recoveries ranged from 20% to 98% and the overall method relative standard deviations were typically less than 20% with some exceptions. Analytical characteristics were determined at 25, 250, and 1000 pg/mL.